Neutrophil alkaline phosphatase score in chronic granulocytic leukaemia: effects of splenectomy and antileukaemic drugs. Issue 7 (July 1975) - Spiers, A S; Liew, A; Baikie, A G
Abstract : Staining with naphthol AS phosphate and Fast Blue BB salt has been used for the estimation of neutrophil alkaline phosphatase (NAP) scores in patients with chronic granulocytic leukaemia (CGL). The very low scores found at diagnosis rise when the disease is treated, and there is some inverse correlation between the NAP score and the absolute neutrophil count. Patients treated intensively developed high NAP scores. Elective splenectomy performed during the chronic phase of CGL is followed by a pronounced but transient neutrophilia and a concurrent striking rise in the NAP score. Similar changes were observed in patients without CGL who underwent splenectomy. These observations can be explained by assuming that newly formed neutrophils in CGL have a normal content of NAP but are rapidly sequestered in non-circulating extramedullary pools, whereas the circulating neutrophil with a typically low NAP content is a relatively aged cell which has lost enzyme activity. In subjects with or without CGL, removal of the spleen, a major site of such pooling, temporarily permits the circulation of newly formed neutrophils but eventually other organs assume the sequestering functions of the spleen. Thus the aberrations of NAP score seen in CGL might be attributable not to an intrinsic cellular defect but to an exaggeration of the granulocyte storage phenomena which also occur in subjects without CGL.